PENERAPAN TEKNIK PEMBELAJARAN THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Intan Kartika Sari; Ardi Yulis; Awalina Barokah; Eva Astuti Mulyani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to find out that the implementation of think pair square to improve students’ learning outcome. This was a classroom action research. The data analysis technique used in this research is qualitative and quantitative data analysis. The results showed that there was an increase in student learning outcomes from before the action, cycle I, and cycle II. Before the action only 9 students (56,25%) achieved the KKM, in cycle I increased to 11 students (68,75%) achieved the KKM, and In cycle II increased to 14 students (87.50%) achieved the KKM. Thus it can be concluded that the application of think pair square learning technique can improve students’ learning outcomes.